Nonomuraea indica sp nov., novel actinomycetes isolated from lime-stone open pit mine, India - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Li, Jie; Nie, Guo-Xing; Tang, Shu-Kun; Al Ruwaili, Jamal; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (Journal of Antibiotics, 2015)
A Gram-positive, aerobic, nonmotile actinomycete strain designated DRQ-2(T) was isolated from the soil sample collected from limestone open pit mine from the Gulbarga region, Karnataka province, India. Strain DRQ-2(T) was identified as a member of the genus Nonomuraea by a polyphasic approach. Strain DRQ-2(T) could be differentiated from other members of the genus Nonomuraea on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence similarity of strain DRQ-2(T) showed highest sequence similarity to Nonomuraea muscovyensis DSM 45913(T) (99.1%), N. salmonea DSM 43678(T) (98.2%) and N. maheshkhaliensis JCM 13929(T) with 98.0%, respectively. Chemotaxonomic properties showing predominant menaquinones of MK-9 (H-4), MK-9(H-2) and MK-9(H-6), major polar lipids comprised diphosphatidylglycerol, phosphatidylmono methyl ethanolamine (PME), phosphatidylethanolamine (PE), hydroxy-PME (OH-PME), hydroxy PE (OH-PEE), phosphatidylglycerol (PG), ninhydrin-positive phosphoglycolipid and unknown phospholipid, fatty acids with major amounts of i-C-16:0, ai-C-15:0 and ai-C-17:0 supported allocation of the strain to the genus Nonomuraea. Results of DNA-DNA hybridization and physiological tests allowed genotypic and phenotypic differentiation of strain DRQ-2(T) from closely related species. The genomic DNA G+C content of the organism was 72.5 mol%. On the basis of phenotypic, chemotypic and molecular characteristics, strain DRQ-2(T) represents a novel species of the genus Nonomuraea, for which the name N. indica sp. nov. is proposed, with type strain DRQ-2(T) (= NCIM 5480(T) = CCTCC AA 209050(T)).